TRADISI NUJUH BULAN KOMUNITAS SUKU SUNDA DI DESA LUBUK KERAPAT KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Surahmah, Rini; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Seven Months is a tradition or custom of traditional ceremonies carried out in the 7th (seventh) month of the first pregnancy for a woman. Seventh monthly implementation is still often carried out by Sundanese people in Lubuk Kerapat Village, Rambah Hilir District, Rokan Hulu Regency. Although this Nujuh Bulan tradition does not exist in Islam, the Sundanese people in particular still carry out the Nujuh Bulan tradition as a gratitude to Allah Subhanahuwata'ala as the creator and the giver of sustenance and gifts to humans and children is one of the many gifts given. The main focus of this research is on the meaning and value of the symbols in the tradition of Nujuh Bulan Sundanese Indigenous people in Lubuk Kerapat Village. This study uses Max Weber's theory of social action, Herbert Blummer's symbolic interactionism, and George Herbert Mead's theory of meaning. The research method used by the author is field research by collecting data through observation and interviews. The sources of the data used were the informants involved and those who were considered to understand the tradition, namely paraji, pregnant women who carried out the Nujuh Bulan tradition, families of pregnant women, and the people of Lubuk Kerapat Village. While the method of data analysis using qualitative methods and the determination of the subject of the research using purposive sampling technique, the researcher makes certain criteria who are used as informants. The people of Lubuk Kerapat village have high values of solidarity and mutual cooperation, therefore life in the village is always harmonious. The tradition of the Sundanese Indigenous Month is that there are procedures for the procession, namely selametan, pengajian, siraman, and finally selling rujak. This tradition also has meaningful symbols. Keywords : Meanings, Tradition, Society, Sundanese